106k views
1 vote
Given that f(x) = x^2– 5x– 36 and g(x) = x + 4, find (f +9)(x) and express

the result in standard form.

Given that f(x) = x^2– 5x– 36 and g(x) = x + 4, find (f +9)(x) and express the result-example-1
User Joe Uhren
by
6.4k points

1 Answer

0 votes

Answer:


\longmapsto \: f(x) = {x}^(2) - 5x - 36 \\ \longmapsto \: g(x) = x + 4 \\ \longmapsto(f + g)(x) \\ = f(x) + g(x) \\ = ( {x}^(2) - 5x - 36) + (x + 4) \\ = {x}^(2) - 5x - 36 + x + 4 \\ = \boxed{ {x}^(2) - 4x - 32}

  • x²-4x-32 (in standard form) is the right answer.
User Muhammedogz
by
6.7k points